Gender and the Rhetoric of Modernity in Spanish America, 1850-1910 - Skinner, Lee Joan (Book collections on Project MUSE., 2016)
The author examines the work of both male and female writers to show how nineteenth-century discourses of modernity and gender overlapped and shaped each other in the Spanish-colonized Americas.